Persistent Hurdles: A Systematic Review of Limit Concept Misconceptions in Undergraduate Calculus - Marthinus Yohanes Ruamba (Department of Mathematics Education Program IPI Garut, 2025)
Konsep limit berfungsi sebagai fondasi kritis untuk kalkulus dan analisis matematika, sekaligus menjadi titik transisi penting menuju pemikiran matematika yang abstrak dan formal. Namun, mahasiswa secara global menghadapi kesulitan yang signifikan dan berulang dalam memahami esensi konsep ini. Tinjauan literatur sistematis ini bertujuan untuk menyintesis bukti-bukti empiris guna mengidentifikasi jenis, pola, dan faktor penyebab miskonsepsi serta kesulitan yang dialami mahasiswa dalam memahami konsep limit. Pencarian sistematis dilakukan pada database Scopus, Web of Science, ERIC, dan Google Scholar untuk studi empiris yang diterbitkan antara tahun 2001 hingga 2024. Proses seleksi dan ekstraksi data mengikuti protokol PRISMA. Data dari studi yang included dianalisis menggunakan analisis tematik, yang menghasilkan 30 studi yang memenuhi kriteria kelayakan. Sintesis dari 30 studi mengungkapkan pola miskonsepsi yang persisten, terutama pemahaman limit sebagai proses dinamis yang tidak terselesaikan, penyamaan limit dengan nilai fungsi, serta kesulitan mendalam dengan representasi berganda dan definisi formal epsilon-delta. Faktor penyebabnya bersifat multidimensi, meliputi aspek kognitif (intuisi sehari-hari, pengetahuan prasyarat lemah), epistemologis (keyakinan instrumentalis tentang matematika), dan pedagogis (pengajaran yang terlalu prosedural). Miskonsepsi tentang limit bersifat kompleks, universal, dan persisten. Diperlukan pendekatan pengajaran yang secara eksplisit dirancang untuk mengkonfrontasi miskonsepsi ini, seperti penggunaan multipresentasi dan assessment diagnostik. Penelitian lebih lanjut sangat diperlukan, khususnya dalam konteks Indonesia, untuk mengembangkan dan menguji efektivitas strategi intervensi yang spesifik. The concept of the limit serves as a critical foundation for calculus and mathematical analysis, while also representing a significant transitional point towards abstract and formal mathematical thinking. However, students globally encounter substantial and recurrent difficulties in grasping the essence of this concept. This systematic literature review aims to synthesize empirical evidence to identify the types, patterns, and causal factors of misconceptions and difficulties experienced by students in understanding the concept of limits. A systematic search was conducted across the Scopus, Web of Science, ERIC, and Google Scholar databases for empirical studies published between 2001 and 2024. The selection and data extraction process followed the PRISMA protocol. Data from the included studies were analyzed using thematic analysis, resulting in the inclusion of 30 studies that met the eligibility criteria. A synthesis of the 30 studies reveals persistent patterns of misconception, particularly the understanding of a limit as an unfinished dynamic process, the conflation of a limit with a function's value, and profound difficulties with multiple representations and the formal epsilon-delta definition. The causal factors are multidimensional, encompassing cognitive aspects (everyday intuition, weak prerequisite knowledge), epistemological aspects (instrumentalist beliefs about mathematics), and pedagogical aspects (overly procedural teaching). Misconceptions regarding limits are complex, universal, and persistent. Teaching approaches explicitly designed to confront these misconceptions are required, such as the use of multiple representations and diagnostic assessments. Further research is urgently needed, particularly within the Indonesian context, to develop and test the effectiveness of specific intervention strategies.